K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1: \(=\left(x-3y\right)\left(x-y\right)-\left(x-3y\right)=\left(x-3y\right)\left(x-y-1\right)\)

4: \(=6x^2-4xy+3xy-2y^2+3x-2y\)

\(=\left(3x-2y\right)\left(2x+y\right)+3x-2y=\left(3x-2y\right)\left(2x+y+1\right)\)

 

 

16 tháng 10 2017

Câu a :

\(\left(3x^2-3y^2\right)+\left(4x-4y\right)=0\)

\(\Leftrightarrow3\left(x^2-y^2\right)+4\left(x-y\right)=0\)

\(\Leftrightarrow3\left(x-y\right)\left(x+y\right)+4\left(x-y\right)=0\)

\(\Leftrightarrow\left(x-y\right)\left[3\left(x+y\right)+4\right]=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x-y=0\\3\left(x+y\right)+4=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=y\\x+y=-\dfrac{4}{3}\Rightarrow x=-\dfrac{4}{3}-y\end{matrix}\right.\)

Vậy \(x=y\) hoặc \(x=-\dfrac{4}{3}-y\)

Câu b :

\(\left(12x^2-3xy\right)+\left(8x-2y\right)=0\)

\(\Leftrightarrow3x\left(4x-y\right)+2\left(4x-y\right)=0\)

\(\Leftrightarrow\left(4x-y\right)\left(3x+2\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}4x-y=0\\3x+2=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\dfrac{y}{4}\\x=-\dfrac{2}{3}\end{matrix}\right.\)

Vậy \(x=\dfrac{y}{4}\) hoặc \(x=-\dfrac{2}{3}\)

a: =3(x^2-y^2-4x+4y)

=3[(x-y)(x+y)-4(x-y)]

=3(x-y)(x+y-4)

b: \(=4x\left(x^2+y^2+2xy-16\right)\)

\(=4x\left[\left(x+y\right)^2-16\right]\)

\(=4x\left(x+y+4\right)\left(x+y-4\right)\)

c: \(=\left(x+4\right)^2-y^2=\left(x+4+y\right)\left(x+4-y\right)\)

d: \(=\left(x^2-1\right)\left(x^2-9\right)=\left(x-1\right)\left(x-3\right)\left(x+1\right)\left(x+3\right)\)

29 tháng 10 2016

a) 6x2.(3x2 - 4x + 5) = 18x4 - 24x3 + 30x2

b) (x - 2y)(3xy + 6y2 + x) = 3x2y + 6xy2 + x2 - 6xy2 - 12y3 - 2xy = -12y3 + 3x2y - 2xy + x2

c) (18x4y3 - 24x3y4 + 12x3y3) : (-6x2y3) = -6x2y3(-3x2 + 4xy - 2x) : (-6x2y3) = 4xy - 3x2 - 2x

20 tháng 10 2019

a) \(x^2y+2xy+y=y\left(x^2+2x+1\right)=y\left(x+1\right)^2\)

b) \(4x^2-4xy-6y^2+6xy=4x\left(x-y\right)+6y\left(x-y\right)=\left(x-y\right)\left(4x+6y\right)\)

\(=2\left(x-y\right)\left(2x+3y\right)\)

c) \(18x^5y+18x^3y-2x^3y^5-2xy^5=18x^3y\left(x^2+1\right)-2xy^5\left(x^2+1\right)\)

\(=\left(x^2+1\right)\left(18x^3y-2xy^5\right)=2xy\left(x^2+1\right)\left(9x^2-y^4\right)=2xy\left(x^2+1\right)\left(3x-y^2\right)\left(3x+y^2\right)\)

d)

20 tháng 10 2019

d) \(-12x^5-12x^3y-3xy^2+36x^4+36x^2y+9y^2=-3x\left(4x^4+4x^2y+y^2\right)+9y\left(4x^4+4x^2y+y^2\right)\)\(=\left(4x^4+4x^2y+y^2\right)\left(9-3x\right)\)